2020
DOI: 10.1002/nop2.681
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of clinical trials affecting anxiety, stress and fear of childbirth in expectant fathers

Abstract: Aim To investigate clinical trials affecting anxiety, stress and fear of childbirth in fathers. Design A systematic literature search was conducted based on Cochrane Collaboration statement recommendation and Preferred Reporting Items for Systematic reviews and Meta‐Analyses checklist. Methods With assistance of Medical Subject Headings, keywords were employed to search for relevant trials. Articles published between November 2000–November 2019 were searched in five electronic databases including PubMed, Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Examples of these fears include fear of not becoming a father, fear of problems that could endanger the health of both mother and child, fear of birth complications or defects, fear of inappropriate behavior by hospital staff, and unpredictability of the delivery process [11,13]. In developed countries, the prevalence of severe fear of childbirth among fathers is estimated to be 13% [3,14,15]. In addition, the prevalence rates of anxiety and depression among fathers during this period are estimated to be 5-15% and 5-10%, respectively [16].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these fears include fear of not becoming a father, fear of problems that could endanger the health of both mother and child, fear of birth complications or defects, fear of inappropriate behavior by hospital staff, and unpredictability of the delivery process [11,13]. In developed countries, the prevalence of severe fear of childbirth among fathers is estimated to be 13% [3,14,15]. In addition, the prevalence rates of anxiety and depression among fathers during this period are estimated to be 5-15% and 5-10%, respectively [16].…”
Section: Introductionmentioning
confidence: 99%
“…Many other elements that make up FOC in men were also declared, such as fear of inability to cope, not being allowed to participate in important decisions, lack of knowledge, unfamiliar healthcare providers and medical environment (19). In the clinical practice, FOC intensities are commonly classified as mild, moderate, severe, and disabling fear (known as tokophobia) (20). Some level of FOC is regarded as normal and adaptive (21), while its exacerbation during pregnancy and childbirth is undesirable (22).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other adverse consequences of elevated paternal FOC may include but not be limited to undermining fathers' capability to support their wives, lowering their self-efficacy to achieve paternal roles, impairing the paternal-infant attachment, jeopardizing the couple relationships, and triggering psychiatric disorders (19,31). Fortunately, there are opportunities to mitigate these negative effects and provide a more pleasant pregnancy and childbirth experience for the distressed father-to-be by identifying fathers at risk of FOC early and providing them with positive childbirth preparation as well as supportive, appropriate, and timely care (11,20).…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of studies, fear of childbirth has been observed in 11–37% of fathers [ 13 16 ]. Since fathers have fewer positive feelings towards pregnancy due to fear of childbirth, it is less likely that they perceive pregnancy as a positive life event [ 14 , 17 ]. Furthermore, fathers with the fear of childbirth have lower General Self-Efficacy (GSE), which may negatively affect their ability to support their wives [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%